Masculinities and the Brunei Chinese “Problem”: The Ambivalence of Race, Gender, and Class in Norsiah Haji Abd Gapar’s Pengabdian - Chin, Grace V.S. (SARE: Southeast Asian Review of English, 2023)
The identity and position of the Chinese are problematic in Brunei Darussalam, where the primary identity of the Malays as “authentic” natives and citizens is upheld by the state ideology of Melayu Islam Beraja (Malay Islamic Monarchy; henceforth MIB). MIB moreover warns of the threat posed by the difference of non-Malays, in this case, the Chinese, while noting their potential contributions to social and economic development. Brunei’s ambivalent treatment of the Chinese Other is reflected in the Malay novel Pengabdian (“Submission,” 1987). Authored by Brunei’s most famous woman writer, Norsiah Abd Gapar, Pengabdian employs the strategies of stereotyping and idealising to produce an MIB-compliant narrative in which the dangers posed by difference, specifically represented by Chinese masculinity, are erased while Brunei Malay masculinity is defended as the hegemonic ideal through the trope of conversion. Using Connell’s theory of masculinities in relation to the strategies of stereotyping and idealising, this article examines how the representations of Brunei Chinese men engage the intersections of race, gender and class that undergird ethnic identities as well as citizenship in Brunei. In so doing, my analysis considers why the Chinese are still treated with such ambivalence and unease, and what this means for interethnic relations on the ground.